ANALYSIS OF TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) AMONG PRE-SERVICE TEACHERS IN THE PPG PROGRAM AT THE INDONESIA UNIVERSITY OF EDUCATION - Annisa, Rahimatul Annisa; Neti Budiwati; Susanti Kurniawati (Universitas Muhammadiyah Surakarta, 2025)
This study was motivated by the fact that the 2019 UKG results were still below standard. The changing times require teachers to be able to integrate technology into the learning process. If this situation continues, it will have an impact on the quality of human resources produced and hinder the ability to keep up with the rapid changes of the times. To produce professional teachers, the process must begin in college (for pre-service teachers), so the abilities of pre-service teachers must be taken into consideration. Studies related to the TPACK profile, especially for pre-service economics teachers, are still rare, so this research is necessary considering that economics is part of social sciences. The population in this study consisted of 58 pre-service economics students at UPI Bandung, using total sampling technique. The method used was quantitative descriptive, where the data obtained was categorized using data tabulation, namely the mean, while the instrument used was a standar instrument adapted from previous research. The results of the study show that the TPK level of pre-service economics teachers is in the good category. Meanwhile, the TCK, TPK, PCK, and TPACK levels of pre-service economics teachers are in the sufficient category. The findings in this study can be used as a basis for educational institutions to design a curriculum that can strengthen TPACK skills, especially for pre-service Pre-service teachers, and provide training that can improve their technological, pedagogical, and content skills.